Preparation and characterization of gallic acid-loaded PLGA hydrogel as teat sealant for preventing mastitis in dry cows - Phornsawat Baipaywad, Raktham Mektrirat, Chawan Manaspon (Journal of Applied Pharmaceutical Science, 2022)
Mastitis or bovine mastitis is an inflammation of the mammary teat caused by an infection. To control mastitis during the dry period, an internal teat sealant was prepared and characterized by encapsulating gallic acid (GA), an antibacterial compound, into an in situ poly(lactic-co-glycolic acid) (PLGA) hydrogel. GA-loaded internal hydrogel teat sealants (IHTSs) were successfully formed in phosphate buffer saline at a 1% weight ratio of GA in a 39% weight ratio of PLGA vehicle. GA was entrapped in the matrix over 30 days. The percentage of GA release was over 48% after 7 days. The in vitro cytotoxicity of the IHTSs against the L929 cell line was evaluated by the medium extraction method. IHTSs showed slight toxicity (reduced 18%–20% cell viability) to the culture due to the 1-methyl- 2-pyrrolidinone solvent in the formulation. However, the overall results did not change the morphology of the L929 cells. Therefore, this preparation clearly showed that PLGA hydrogels may be used for the long-term release of GA internal teat sealant to prevent mastitis in dry cows.
Keywords: Bovine mastitis, drug delivery system, gallic acid, hydrogel, PLGA